Communications Training Needs in Arkansas' Agritourism Industry - Jefferson Miller; Stacey McCullough; Daniel Rainey; Biswaranjan Das (Journal of Applied Communications, 2012)
Agritourism has emerged globally as a tool to diversify farm income, and the need for non-formal educational programming in this area has become obvious. In Arkansas, Cooperative Extension educators have lacked empirical data to guide program development. One clear need, according to literature, is for operators to improve marketing communications skills. Researchers surveyed agritourism operators in Arkansas to describe demographics, educational needs (especially related to marketing communications), and educational delivery preferences. Results indicated that operators were typically older than 50 and that 60% had been in operation for longer than 10 years. Key issues and educational needs related to marketing communications included promotion and marketing, advertising, media relations, and signage. Communications tactics commonly used by the respondents included word-of-mouth (WOM); websites; print, radio, and television advertising; and local media relations. Preferred delivery methods for educational programming related to agritourism included periodic newsletters, regional workshops, and news releases.
Keywords: agritourism; tourism; agricultural communications; marketing communications; rural development; risk management; survey research